Patient teaching: Short peripheral I.V. catheters. Issue 11 (November 2015) - Spencer, Sharon; Gilliam, Patricia
Abstract : What do your nurses need to know to provide education on caring for, monitoring, and preventing injury to peripheral venous access sites?